Design and Evaluation of Canva for Education–Based Interactive Learning Media for Strengthening Students’ Mathematical Conceptual Understanding - Fahrul Purnama; Reisya Rahma Nabilah; Sisien Elsa Nadia; Hana Lastiar Olivia Sagala; Merlina Dwi Astuti; Zahra Nur Kamilah; Adi Ihsan Imami (Jurnal Didactical Mathematics, 2026)
Students’ difficulties in understanding mathematical concepts, particularly negative integer operations, are often rooted in teacher-centered instructional practices that provide limited opportunities for conceptual exploration and active engagement. This study aimed to develop and evaluate interactive mathematics learning media based on Canva for Education to enhance students’ conceptual understanding. Employing a Research and Development (R&D) approach guided by the ADDIE model, the study was conducted through five stages: analysis, design, development, implementation, and evaluation. The analysis stage involved diagnostic testing, classroom observations, and a review of school readiness, revealing that 65.62% of students experienced conceptual difficulties. The developed product was an interactive PowerPoint-based learning medium that focused on conceptual visualization, guided examples, and interactive quizzes. Expert validation confirmed high content validity and instructional quality, while revisions were made to improve interactivity and technical usability. The implementation involved a classroom trial with 32 Grade VII students at a junior high school in Karawang. Results indicated a significant improvement in learning outcomes, with average test scores increasing from 60.78 (pre-test) to 76.73 (post-test), representing a gain of 15.95 points (26.2%). The practicality evaluation yielded an overall score of 80.93%, categorized as practical, supported by positive student responses and adequate teacher readiness. These findings demonstrate that Canva for Education–based interactive learning media developed using the ADDIE model are valid, practical, and effective in supporting students’ conceptual understanding of mathematics, offering a promising instructional solution for secondary education contexts.